2012
DOI: 10.1177/0091270011407194
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Panax ginseng on Cytochrome P450 (CYP)3A and P‐glycoprotein (P‐gp) Activity in Healthy Participants

Abstract: A number of herbal preparations have been shown to interact with prescription medications secondary to modulation of cytochrome P450 (CYP) and/or P-glycoprotein (P-gp). The purpose of this study was to determine the influence of Panax ginseng on CYP3A and P-gp function using the probe substrates midazolam and fexofenadine, respectively. Twelve healthy subjects (8 males) completed this open label, single sequence pharmacokinetic study. Healthy volunteers received single oral doses of midazolam 8 mg and fexofena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 43 publications
2
81
1
3
Order By: Relevance
“…In the current study, we showed that GSE significantly attenuated DSS-induced colitis, which is associated with repressed NF-kB activity and restored PXR and CYP3A mRNA expression in the inflamed colon. Although it has previously been reported that Panax ginseng influence CYP3A activity (Malati et al, 2012), we confirmed that ginsenosides had no effect on Pxr and Cyp3a11 mRNA expression in the healthy mice, which is consistent with the findings from in vitro LS174T cells and the results from other groups (Gurley et al, 2002;Anderson et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we showed that GSE significantly attenuated DSS-induced colitis, which is associated with repressed NF-kB activity and restored PXR and CYP3A mRNA expression in the inflamed colon. Although it has previously been reported that Panax ginseng influence CYP3A activity (Malati et al, 2012), we confirmed that ginsenosides had no effect on Pxr and Cyp3a11 mRNA expression in the healthy mice, which is consistent with the findings from in vitro LS174T cells and the results from other groups (Gurley et al, 2002;Anderson et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…However, Malati's group suggested that (using fexofenadine as a probe substrate) ginseng did not alter P-gp function in healthy volunteers. (31) Two ideas may explain the difference between our data. First fexofenadine as a P-gp probe is not specifi c. The transport system for fexofenadine includes not only P-gp but also other transporters.…”
Section: Discussionmentioning
confidence: 77%
“…Comparison of pharmacokinetic parameter values of midazolam was calculated and compared before and following the administration of Panax ginseng. As illustrated in Figure 4, the findings revealed significant reduction for midazolam area under the concentration-time curve from zero to infinity, half-life and maximum concentration [104]. Also, American ginseng (Panax quinquefolius)…”
Section: Several Herbs Have Been Used In the Management Of Depressionmentioning
confidence: 91%
“…Panax ginseng is a widely used herbal medicine, notably used for its antidepressant effect. A study investigated the influence of Panax ginseng on CYP3A function using the probe midazolam as a substrate probe [104]. Comparison of pharmacokinetic parameter values of midazolam was calculated and compared before and following the administration of Panax ginseng.…”
Section: Several Herbs Have Been Used In the Management Of Depressionmentioning
confidence: 99%